2020
DOI: 10.1021/acs.langmuir.0c02401
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Wettability Control of Honeycomb Films by UV–O3-Assisted Sol–Gel Coating

Abstract: Wettability control of porous materials is significant in lateral flow immunoassay, microfluidic systems, microdroplet manipulation, and so on. In this report, formation of metal oxide layers on self-organized polymer honeycomb films to control surface wettability by simple sol–gel coating and UV–O3 treatment was demonstrated. By the combination of bottom-up and top-down processes, silica thin layers can be formed by retaining their original three-dimensional honeycomb structures. Furthermore, photopatterning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Recently, we found that silica-coated honeycomb films can be prepared by simple coating of tetraethyl orthosilicate (TEOS) onto polymer honeycomb films, followed by ultraviolet−ozone (UV−O 3 ) treatment. 37 In the present work, using this silica-coated honeycomb film as a template, we prepared Mg 2 Si honeycomb films via a Mg vapor annealing treatment. 31 The effect of the annealing temperature on the structural and chemical composition of the annealed samples is discussed, and we demonstrate the synthesis of highly porous Mg 2 Si via a simple UV−O 3 annealing treatment.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we found that silica-coated honeycomb films can be prepared by simple coating of tetraethyl orthosilicate (TEOS) onto polymer honeycomb films, followed by ultraviolet−ozone (UV−O 3 ) treatment. 37 In the present work, using this silica-coated honeycomb film as a template, we prepared Mg 2 Si honeycomb films via a Mg vapor annealing treatment. 31 The effect of the annealing temperature on the structural and chemical composition of the annealed samples is discussed, and we demonstrate the synthesis of highly porous Mg 2 Si via a simple UV−O 3 annealing treatment.…”
Section: Introductionmentioning
confidence: 94%
“…TEOS solution was also used by Yabu et al. [ 74 ] for sol–gel reaction onto a pre‐formed HC film from a blend of PB and an acrylamide based amphiphilic copolymer. In this study, initial polymer was used as a pattern support to bring the porous shape to silica structure while the organic part was finally removed by UVO treatment to recover a fully inorganic structure.…”
Section: Honeycomb Silica Films Formationmentioning
confidence: 99%
“… 30 , 31 The sol–gel and layer-by-layer methods are examples of useful and relatively scalable methods to create hierarchical nanostructures. 32 35 Particulate coatings are a type of structured coating where the structures are established by micro- or nanoparticles. One example of bio-based particulate coatings is the layer-by-layer approach to attach wax particles onto wood, textiles, or other cellulosic substrates using a cationic polymer or particle as binder.…”
Section: Introductionmentioning
confidence: 99%
“…Micro- and nanostructured coatings have gained attention because of their often excellent anticorrosion, antibacterial, anti-icing, and UV-shielding properties . The high surface roughness of nanostructured coatings is one important factor contributing to their exceptional hydrophobicity. , The sol–gel and layer-by-layer methods are examples of useful and relatively scalable methods to create hierarchical nanostructures. Particulate coatings are a type of structured coating where the structures are established by micro- or nanoparticles. One example of bio-based particulate coatings is the layer-by-layer approach to attach wax particles onto wood, textiles, or other cellulosic substrates using a cationic polymer or particle as binder. , Electrostatically bound coatings such as these can be used extremely sparingly while providing excellent hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%